Good Slang or Bad Slang? Embedding Internet Slang in Persuasive Advertising - Liu, Shixiong; Gui, Dan-Yang; Zuo, Yafei; Dai, Yu (Frontiers in Psychology, 2019)
Internet slang is a new language with innovative and novel characteristics, and its use can be considered a form of creative advertising. Embedding internet slang into advertisements can thus enhance their creative quality and increase the attention paid to them. In this study, we examined the effect of the characteristics of internet slang on attention to advertisements, brand awareness, product evaluation, and attitudes toward advertising by conducting two empirical studies, one utilizing eye-tracking experiments and the other utilizing questionnaires. We found that using internet slang in advertising significantly increased audience attention compared with standard language, but did not necessarily improve product evaluation and brand awareness for various types of goods. We discovered code-switching effects of psycholinguistics existed in standard language and its variant (internet slang). Our findings can guide advertisers in selecting the embedded language that can be effective in achieving their desired advertising effect. Our findings also indicate that the excessive use of internet slang may have a negative effect on brand and product evaluation.